Short Communication: Genetic diversity of fumonisin producing Fusarium isolates from rice using PCR-RFLP of IGS-rDNA region - SHUBHRANSU NAYAK; URMILA DHUA; APURBA CHHOTARAY; SOMA SAMANTA; CHANDAN SENGUPTA (Biodiversitas Journal of Biological Diversity, 2018)
Nayak S, Dhua U, Chhotaray A, Samanta S, Sengupta C. 2018. Short Communication: Genetic diversity of fumonisin producing Fusarium isolates from rice using PCR-RFLP of IGS-rDNA region. Biodiversitas 19: 621-626. Fusarium verticillioides (Sacc.) and related species produce carcinogenic mycotoxin known as Fumonisins in several agricultural crops including rice. However, this principal food crop has been infected by genetically diverse Fusarium species. Odisha belongs to the coastal part of India and many popular rice varieties are in the food chain in this region. Many Fusarium species producing fumonisins have been found to be associated with these rice varieties. Hence, the genetic diversity of twenty eight Fumonisin producers and non producers of Fusarium pathogens in this region was carried out in the current study. The IGS regions of 28 Fusarium isolates (both fumonisin producing and non producing) were amplified and the PCR products were restriction digested with ECoRI and HhaI. The digested products were separated on PAGE and bands were visualized by Silver Nitrate Staining. The 28 isolates could be separated into 14 IGS haplotypes. The lowest similarity was detected to be of 33% between F40 and F47. A group containing 14 isolates represented the biggest haplotypes. The isolates in which the FUM gene had not been detected (fumonisin non producer) were in a separate group having 90% similarity with each other and placed consistently in separate branch from others. Presence of unique band for this group was observed at 1650bp where as absence of specific bands was observed at 380bp and 300bp. The result of this study indicated a high degree of genetic variation among 28 Fusarium isolates. PCR RFLP of IGS region was also found to be useful for diversity study in Fusarium.